Research progress on the pathogenesis of Alzheimer disease and microbes - ZHA Yanan; WANG Feng; HAN Peipei (Shanghai yufang yixue, 2023)
Alzheimer disease （AD） is a progressive neurodegenerative disease that often occurs in the elderly. The main symptoms of AD patients are cognitive decline， especially memory deficits， communication problems， impaired performance of activities of daily living， and other behavioral and psychological abnormalities. AD is generally divided into familial AD and sporadic AD. The signature features of AD are the presence of amyloid-beta proteins in extracellular plaques. Senile plaques formed by accumulation of Aβ insoluble fragments and intracellular accumulation of highly phosphorylated tau are neurofibrillary tangles. There is a lot of scientific evidence to confirm that the development of the two signature features of AD may be related to naturally occurring microbes in the human body. This paper reviews the mechanism of intestinal， oral and fungal microbiota involved in the development and progression of AD.